Ruxolitinib Ameliorates Airway Hyperresponsiveness and Lung Inflammation in a Corticosteroid-Resistant Murine Model of Severe Asthma - Subramanian, Hariharan; Hashem, Tanwir; Bahal, Devika; Kammala, Ananth K.; Thaxton, Kanedra; Das, Rupali (Frontiers in Immunology, 2021)
Asthma prevalence has increased considerably over the decades and it is now considered as one of the most common chronic disorders in the world. While the current anti-asthmatic therapies are effective for most asthma patients, there are 5-10% subjects whose disease is not controlled by such agents and they account for about 50% of the asthma-associated healthcare costs. Such patients develop severe asthma (SA), a condition characterized by a dominant Th1/Th17 cytokine response that is accompanied by Type 2 (T2)-low endotype. As JAK (Janus Kinase) signaling is very important for the activation of several cytokine pathways, we examined whether inhibition of JAKs might lessen the clinical and laboratory manifestations of SA. To that end, we employed a recently described murine model that recapitulates the complex immune response identified in the airways of human SA patients. To induce SA, mice were sensitized with house dust mite extract (HDME) and cyclic (c)-di-GMP and then subsequently challenged with HDME and a lower dose of c-di-GMP. In this model, treatment with the JAK inhibitor, Ruxolitinib, significantly ameliorated all the features of SA, including airway hyperresponsiveness and lung inflammation as well as total IgE antibody titers. Thus, these studies highlight JAKs as critical targets for mitigating the hyper-inflammation that occurs in SA and provide the framework for their incorporation into future clinical trials for patients that have severe or difficult-to manage asthma.